Neuroimaging and the Complexity of Capital Punishment - Snead, O. Carter (2007)
The growing use of brain imaging technology to explore the causes of morally, socially, and legally relevant behavior is the subject of much discussion and controversy in both scholarly and popular circles. From the efforts of cognitive neuroscientists in the courtroom and the public square, the contours of a project to transform capital sentencing both in principle and in practice have emerged. In the short term, these scientists seek to play a role in the process of capital sentencing by serving as mitigation experts for defendants, invoking neuroimaging research on the roots of criminal violence to support their arguments. Over the long term, these same experts (and their like-minded colleagues) hope to appeal to the recent findings of their discipline to embarrass, discredit, and ultimately overthrow retributive justice as a principle of punishment. Taken as a whole, these short- and long-term efforts are ultimately meant to usher in a more compassionate and humane regime for capital defendants. This Article seeks to articulate, analyze, and provide a critique of this project according to the metric of its own humanitarian aspirations. It proceeds by exploring the implications of the project in light of the mechanics of capital sentencing and the heterogeneous array of competing doctrinal rationales in which they are rooted. The Article concludes that the project as currently conceived is internally inconsistent and would, if implemented, result in ironic and tragic consequences, producing a death penalty regime that is even more draconian and less humane than the deeply flawed framework currently in place